The Routledge handbook of women and ancient Greek philosophy
1 online resource
Keywords: The Routledge Handbook of Women and Ancient Greek Philosophy is an essential reference source for cutting-edge scholarship on women, gender, and philosophy in Greek antiquity. The volume features original research that crosses disciplines, offering readers an accessible guide to new methods, new sources, and new questions in the study of ancient Greek philosophy and its multiple afterlives. Comprising 40 chapters from a diverse international group of experts, the Handbook considers questions about women and gender in sources from Greek antiquity spanning the period from 7th c. BCE to 2nd c. BCE, and in receptions of Greek antiquity from the Roman Imperial period, through the European Renaissance to the current day. Chapters are organized into five major sections: I. Early Greek antiquity - including Sappho, Presocratic philosophy, Sophists, and Greek tragedy - 700s-400s BCEII. Classical Greek antiquity - including Aeschines, Plato, and Xenophon - 400s-300s BCEIII. Late Classical Greek to Hellenistic antiquity - including Cyrenaics, Cynics, the Hippocratic corpus, and Aristotle - 300s-200s BCEIV. Late Greek antiquity to Roman Imperial period - including Pythagorean women, Stoics, Pyrrhonian Skeptics, andlate Platonists - 200s BCE to 700s CEV. Later receptions - including Shakespeare, the European Renaissance, Anna Julia Cooper, W.E.B. DuBois, Jane Harrison, Sarah Kofman, and Toni Morrison The Routledge Handbook of Women and Ancient Greek Philosophy is a vital resource for students and scholars in philosophy, Classics, and gender studies who want to gain a deeper understanding of philosophy's rich past and explore sources and questions beyond the traditional canon. The volume is a valuable resource, as well, for students and scholars from history, humanities, literature, political science, religious studies, rhetorical studies, theatre, and LGBTQ and sexuality studies.